Fathers and grandmothers experiences participating in nutrition peer dialogue groups in Vihiga County, Kenya. (9th July 2021) - Thuita, Faith; Mukuria, Altrena; Muhomah, Teresia; Locklear, Kamryn; Grounds, Samantha; Martin, Stephanie L.
Abstract: Grandmothers and fathers are key influencers of maternal and child nutrition and are increasingly included in interventions. Yet, there is limited research exploring their experiences participating in interventions. This study reports on findings from a qualitative process evaluation of a quasi‐experimental study that we conducted with grandmother and father peer dialogue groups to support maternal, infant and young child feeding practices in western Kenya. The aim was to explore grandmother and father experiences participating in interventions and how participation influences care and feeding practices. Grandmother and father peer educators received training to facilitate discussions about maternal and child nutrition, HIV and infant feeding, family communication, and family members' roles. Father peer educators also received training on gender inequities and power dynamics. In the original quasi‐experimental study, the intervention was associated with increased social support and improvements in some complementary feeding practices. The process evaluation explored participants' experiences and how participation influenced infant care and feeding practices. We used Atlas.ti to thematically analyse data from 18 focus group discussions. The focus group discussions revealed that grandmothers and fathers valued their groups, the topics discussed and what they learned. Grandmothers reported improved infant feeding and hygiene practices, and fathers reported increased involvement in child care and feeding and helping with household tasks. Both described improved relationships with daughters‐in‐law or wives. This study highlights the importance of engaging influential family members to support child nutrition and identifies factors to build cohesion among group members, by building on grandmothers' roles as advisors and expanding fathers' roles in nutrition through gender transformative activities.